Scaled model of a steel moment resisting frame for a shaking table test - Chavez, Dennis Noel L.
Structural modeling is a method in which behavior and response of structures under different types of loadings are studied, either through actual experimentation or analytical simulation. Accompanying this are proper similitude laws ensuring first-order similarity throughout the structure since complete similarity is highly improbable. Parameters which maintain first-order similarity is prioritized in this research while developing the procedure which was used to model the structure. This procedure was based on two similitude laws developed specific for steel structures under seismic forces and is then applied on the three story single bay steel frame structure studied at the University of California, Berkeley. The procedure was verified through the use of analytical software, SAP 2000, but was limited to the determination of quantities prioritized due to first order similarity. After simulation, the results show that the procedure developed was adequate for the structure up to some extent after the results of the analytical simulation are scaled up and compared to that of the full scale experiment. The results such as the moment vs. strain and per floor absolute acceleration showed that the procedure is adequate up to an extent allowed by the first order similarity. However, the simulation's spectral acceleration graphed against the natural period showed significant error when the compared to the full scale test. This is attributed to the variation in the actual design and construction of the prototype model with the modeling of the scaled structure on the software. It is recommended that if there are similar researches conducted, other variables are tested and as well as the analytical software for earthquake simulation. Actual testing of the scaled model, while changing the scope to accommodate other quantities, is also suggested to compare to and validate software analysis.